Gonadotropin dependent premature pubertal development in girls. Description of clinical cases - A. V. Vitebskaya; J. R. Amshinskaya; O. V. Shuminov (Сеченовский вестник, 2017)
Precocious puberty (PP) is one of the most common abnormalities of pubertal development in children. Typical PP features are: accelerated physical development, premature development of secondary sexual characteristics, early growth plates closure and formation of short stature in adult age. The article tempts to demonstrate the importance of early diagnostics of true PP in girls, the basic principles of treatment and dispensary observation. We have analyzed two clinical cases where both patients had idiopathic gonadotropin dependent PP, the diagnosis was defined at the same age, but the duration of the disease at the time of diagnosis was different. The patients received therapy with long-acting analogues of luteinizing releasing hormone, the effectiveness of therapy was confirmed by clinical and laboratory tests. Timely started treatment to our patients contributed to the normalization of the growth forecast.